Enhanced chemotherapy efficacy by co-delivery of shABCG2 and doxorubicin with a pH-responsive charge-reversible layered graphene oxide nanocomplex. Issue 31 (15th July 2015) - He, Yuling; Zhang, Lifen; Chen, Zhenzhen; Liang, Yong; Zhang, Yushun; Bai, Yanli; Zhang, Jing; Li, Yanfeng
Abstract : pH responsive charge-reversible GO–PEI–PEG/DOX/CS-Aco/PEI/shABCG2 nanocomplexes for efficient intracellular DOX and shABCG2 co-delivery. Abstract : In this study, we constructed a layered graphene oxide (GO) nanocomplex with pH-responsive charge-reversible chitosan-aconitic anhydride (CS-Aco), biocompatible polyethylene glycol (PEG) and low molecular weight polyethylenimine (PEI). This was employed as a novel delivery system for intracellular pH-triggered DOX and short hairpin RNA (shRNA) controlled release and synergistic therapy. The nanocomplex GO–PEI–PEG/DOX/CS-Aco/PEI/shRNA exhibited high drug and shRNA loading, and good stability at physiological pH. In an acid pH environment, the negatively charged CS-Aco layer hydrolyzed into positively charged chitosan, causing the shielding layers of the nanocomposite to loosen. The disassembled GO–PEI–PEG/DOX and chitosan efficiently ruptured the endosome, significantly facilitating the release of DOX and PEI/shRNA into the cytoplasm, and then the shRNA disassembled rapidly because of its weak electrostatic interactions with the short PEI chains. Consequently, GO–PEI–PEG/DOX/CS-Aco/PEI/shRNA exhibited excellent shABCG2 and DOX co-delivery efficiency in HepG2 cells, which was better than that of GO/DOX and the non-charge-reversible GO–PEI–PEG/DOX/CS-Car/PEI/shRNA nanocomplex. Furthermore, this novel nanocomplex had high efficiency in silencing ABCG2 expression, and exhibited a significant synergistic efficacy in chemotherapy.